Environmental, Social and Governance Disclosure Scores and Tax Avoidance - Adrian Teja (Jurnal Ilmiah Akuntansi, 2024)
This paper aims to understand the effect of Environmental, Social, and Governance (ESG) disclosure scores on tax avoidance. The sample consists of public firms listed on the Indonesia Stock Exchange, excluding those in the financial services industry, for the period 2015-2021. We employ panel data regression methods, with the dependent variable being the total of deferred tax assets and liabilities and the independent variable being the Bloomberg ESG disclosure scores. The effect of Bloomberg ESG disclosure scores on tax avoidance is controlled by firm leverage, profitability, growth, and size. Our findings indicate that higher Bloomberg ESG disclosure scores have a positive effect on deferred tax assets relative to deferred tax liabilities. This suggests that firms with high Bloomberg ESG disclosure scores contribute to indirect stakeholders, reflecting a broader commitment beyond direct stakeholders. Additionally, we do not find statistical evidence of a significant effect of a firm's financial constraints and growth opportunities on the deferred tax assets relative to deferred tax liabilities. These results imply that tax avoidance is more influenced by a firm's commitment to ESG principles rather than its financial capabilities and growth opportunities. This research provides valuable insights for policymakers and corporate managers, highlighting the importance of ESG disclosure in shaping tax-related strategies and demonstrating a firm’s commitment to broader stakeholder engagement.